Sexual Selection and the Evolution of Male Reproductive Traits in Benthic Octopuses - Ibáñez, Christian M.; Pérez-Álvarez, Javiera; Catalán, Jennifer; Carrasco, Sergio A.; Pardo-Gandarillas, M. Cecilia; Rezende, Enrico L. (Frontiers in Physiology, 2019)
Competition between same-sex organisms, or intra-sexual selection, can occur before and after mating, and include processes such as sperm competition and cryptic female choice. One of the consequences of intra-sexual selection is that male reproductive traits tend to evolve and diverge at high rates. In benthic octopuses, females often mate with more than one male in a single reproductive event, opening the venue for intra-sexual selection at multiple levels. For instance, males transfer spermatophores through hectocotylus, and can remove the spermatophores left by other males. Considering the limited evidence on post-copula competition in benthic octopuses, and the potential to affect the evolution of reproductive traits within octopodids, we put this hypothesis to a test employing a phylogenetic comparative approach. We combined data on hectocotylized arm length (HAL), ligula length (LL), spermatophore length (SL) with a Bayesian molecular phylogeny of 87 species, to analyse how reproductive traits have diverged across lineages and covary with body size (mantle length; ML). First, additionally to ML, we estimated the phylogenetic signal (λ) and mode of evolution (κ) in each reproductive trait. Second, we performed phylogenetic regressions to quantify the association among reproductive traits and their co-variation with ML. This analysis allowed us to estimate the phenotypic change along a branch into the phylogeny, and whether selection may have played a role in the evolution and diversification of specific clades. Estimations of λ were always high (> 0.75), indicating concordance between the traits and the topology of the phylogenetic tree. Low values of κ (< 1.0) suggested that evolution depends on branch lengths. All reproductive traits exhibiting a positive relation with ML (β> 0.5 in all cases). Overall, evolutionary rate models applied to the SL-ML regression suggested that octopuses of the family Megaleledonidae have evolved larger spermatophores than expected for their size. The regression HAL-ML indicated that HAL was more variable in Megaleledonidae than in the remaining clades, suggesting that the high divergence across species within this group might partially reflect intra-sexual selection. These results support the hypothesis that sexual selection may account for the divergence in reproductive traits of male octopuses in some lineages.